(untitled) (Bangladesh Journal of Medical Science, 2018)
Background: Molybdenum- 99 is a parent isotope of Technetium-99m (99mTc) as intermediate to diagnosis and radiation treatment. This production is made according to irradiation of Molybdenum-98 with thermal neutrons. The cycle comprises a complex of MoO3 or the percentage of Mo-98 is 24.13%, this compressed mixture in an irradiation capsule of aluminum; the latter is disposed in the central thimble of a nuclear reactor so that the thermal neutron flux is at a maximum in order to generate 98Mo to 99Mo by nuclear reaction of (n, γ) where the crosssection of molybdenum is (0.13 ± 0.0013) barn. Method: The purpose of this study is to validate of MoO3 target that will be used for the production of Molybdenum-99 in the central thimble irradiation position of the TRIGA Mark II research reactor at CNESTEN (Morocco National Center for Nuclear Energy, Sciences and Techniques), The thermal neutron flux used for activity calculation of Mo-99 used reactor of research TRIGA Mark-II is 3.1 1011 n/cm²s at 250 KW, 2.4E+13 n/cm2s at 1.1 MW and 3.01 1013n/cm²s at 2MW, we are using Fortran-90 code for calculate the activity. Result: The result’s finding was validated by other studies. Bangladesh Journal of Medical Science Vol.17(4) 2018 p.567-572